FOXM1 Promotes Head and Neck Squamous Cell Carcinoma via Activation of the Linc-ROR/LMO4/AKT/PI3K Axis - Ma, Xiao; Zhang, Hong; Li, Qian; Schiferle, Erik; Qin, Yao; Xiao, Suifang; Li, Tiancheng (Frontiers in Oncology, 2021)
Background/Aim: Previous literature has implicated the sustained expression of FOXM1 in numerous human cancers, including head and neck squamous cell carcinoma (HNSCC). The current study aimed to elucidate the function and regulatory mechanism of FOXM1 in HNSCC. Methods: Western blot and RT-qPCR methods were performed to evaluate the expression of Linc-ROR, FOXM1, and LMO4 in HNSCC tissue samples and cells. The binding between FOXM1 and Linc-ROR was analyzed using a ChIP assay. Various cellular processes including proliferation and invasion abilities were assessed following alteration of FOXM1, Linc-ROR and LMO4 expression in HNSCC cells. Xenograft mouse models were established to validate the in vitro findings. Results: Linc-ROR and FOXM1 were highly expressed in HNSCC tissues and cells. FOXM1 operated as a potential transcription factor to bind to the promoter region of Linc-ROR. Linc-ROR and FOXM1 exhibited high expression levels in both the clinical tissue samples as well as the HNSCC cells, which could facilitate the proliferation and invasion of HNSCC cells. Linc-ROR upregulated the expression of LMO4 and promoted activation of the AKT/PI3K signaling pathway, thus stimulating the proliferation and invasion of HNSCC cells. Silencing of Linc-ROR brought about a contrasting effect relative to that seen when FOXM1 was overexpressed in HNSCC in vivo. Conclusions: Overall, FOXM1 promoted the expression of Linc-ROR and induced the activation of the LMO4-dependent AKT/PI3K signaling pathway, thus facilitating the occurrence and development of HNSCC.